corona100d: German-language Twitter dataset of the first 100 days after Chancellor Merkel addressed the coronavirus outbreak on TV - Jonas Rieger; Gerret von Nordheim (TU Dortmund University, Dortmund Center for Data-based Media Analysis (DoCMA), 2021)
In this paper, we present a German-language Twitter dataset related to the Covid-19 pandemic. We show how the R (R Core Team 2020) package rtweet (Kearney 2019) and a combination of keywords can be used to create the dataset and provide a way to rehydrate most of the tweets. The dataset consists of 3 699 623 tweets from 2020/03/19 to 2020/06/26 and was constructed from hourly API requests of 50 000 tweets. In a brief analysis, we give first insights into the dataset and provide approaches that can be refined in further research.
Keywords: 330; Covid-19; SARS-CoV-2; scraper; data; text; developer; dev; Twitter